2017
DOI: 10.5742/mewfm.2017.93094
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus : Knowledge, Management and Complications : Survey Report from Faisalabad, Pakistan

Abstract: Introduction: Diabetes mellitus is a major health problem worldwide that increases morbidity and mortality rates due to its complications. The objective of this study was to assess the knowledge of diabetic patients about their disease, its complications and management. Methods: A cross-sectional study was conducted in outpatient clinics of Faisalabad, Pakistan during March to May 2017. A total of 691 diabetic patients (verified from physician, medical records) were consecutively approached and a pretested, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Studies have reported that knowledge of and awareness about a disease can have positive effects on patients’ health outcomes, such as increased compliance to the medication and less chances of hospital admission etc. [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that knowledge of and awareness about a disease can have positive effects on patients’ health outcomes, such as increased compliance to the medication and less chances of hospital admission etc. [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…If there is knowledge regarding the disease along with awareness as reported by some studies there will be less chances of patient noncompliance and positive health outcomes can be achieved by the early diagnosis and appropriate treatment [10,11]. The burden of the disease would be reduced and this is possible with the improved disease awareness, that will play a vital role for the management of disease and also to reduce disease related complications [8].…”
Section: Introductionmentioning
confidence: 99%